Pengaruh Ekstrak Daun Suji (Dracaena angustifolia) terhadap PH Lambung Tikus Jantan Rattus Norvegicus yang Diinduksi NSAID - Dita Sukmaya Prawitasari; Rivan Virlando Suryadinata; Ni Luh Riska Dewi Sarmitavati (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2021)
ABSTRACTBackground of Study: The widespread use of non-steroidal anti-inflammatory drugs (NSAIDs) as analgesic, antipyretic and anti-inflammatory agents still causes some worries in the polulation related to side effects, especially gastric ulcers. Suji leaf (Dracaena angustifolia) is a plant that well known as a food coloring also known contain flavonoids, saponins and phenolics that have the potential as antioxidants and anti-inflammatory. The purpose of this study was to determine the effect of suji leaf extract on gastric pH of male Rattus norvegicus rats induced by NSAIDs.Methods : This study was a laboartory experimental research using Randomized Controlled Trial with Post-test Only Control Group Design. Thirty male rats (Rattus norvegicus) divided into 6 groups, i.e normal control group (KN), negative control (K-), positive control (K+), and three treatment groups with Suji leaf extract dose 50mg/kgbw (KU1), 100mg/kgBW (KU2) and  group with Suji leaf extract dose 200mg/kgbw (KU3) for 14 days once daily after induction of NSAID (aspirin dose 200 mg/kgbw for 5 days) at the Animal Laboratory Faculty of Medicine, Universitas Surabaya. Gastric pH was measured after the rats fasted and sacrificed. Data were analyzed statistically by using One Way ANOVA test and LSD (Least Significant Difference).Results : The results showed that there was no significant difference between each group KU1, KU2 and KU3 on gastric pH of rats induced by NSAIDs (p 0.05). The lowest mean gastric pH level was in the K(+) group.Conclusion : The administration of suji leaf extract did not show a significant difference to the gastric pH of male Rattus noervegicus rats induced by NSAIDs.Keywords : Suji leaf; gastric ulcer; NSAID; gastric pH